The Management of Youth Employment in a Lifelong Engineering Education System - Morozova, Marina V.; Kust, Tatyana S.; Sokolova, Elvira Y.; Osipova, Svetlana I.; Gafurova, Natalya Vladimirovna; Vaganova, Valentina I.; Ovchinnikov, Vladimir A.; Agavelyan, Ruben O. (International Review of Management and Marketing, 2016)
The formation of lifelong engineering (technical) education based on the interaction and collaboration among education, industrial plants and business structures contributes to the creation of a youth employment management system which, in turn, makes a contribution to the development of human potential that will be able to satisfy the modern social and economic needs of a country. The system of lifelong engineering education allows: to create conditions for pupils' professional orientation toward technical and engineering specialization in their future vocational training; to provide conditions to engineering university students for the formation of their skills, habits and professional competence enabling to solve professional problems in real industrial production environment with the use of high-technology equipment; to manage and control the graduates' placement through the solution of the above mentioned tasks by increasing the number of young specialists being employed within one year after graduating from a university and getting an education. The system of lifelong engineering (technical) education enables to cover a large segment of the population by vocational training programs, retraining, post-secondary technical and advanced training on the basis of multi-functional centers of applied qualifications and educational-sectoral clusters. Practical outcomes of the above specified work will be the formation of an efficient youth employment management system and the provision of Russian economy with high-qualified personnel in the priority directions of modernization and technological development. Upon the obtained results of this research some scientific problems and priority directions requiring further consideration can be distinguished: the study and generalization of foreign and Russian engineering university experience concerning the development of youth employment management system through the implementation of innovative models of engineering education organization; seeking new areas of activity which will have a positive impact on the quality of lifelong technical education and youth employment. The material of the article can be useful and significant for specialists and managers of educational organizations, job centers and production-and-training centers by the determination of forms and methods of interaction, as well as selection and arrangement of the instructional content of technicians-and-engineers' collaborative training. Keywords: lifelong education, youth employment, interaction. JEL Classifications: A20, I21, I28